Google Trend as a Tool for Market Analysis in Healthcare - Rahmawati, Nahardian Vica; Munaa, Nihayatul; Saputra, Muhamad Ganda; Ummah, Faizatul; Nurdiana, Fara; Lutfi, Ahmad Mustofa (P3M Politeknik Negeri Jember, 2023)
This study aimed to analyze the market and the opportunity of Child Development Clinic using Google Trends and the effect of regulation on relative search volume (RSV). Child development has become a national priority since the issuance of regulation number 72 of 2021 concerning accelerating the reduction of stunting. The research used descriptive and analytic quantitative method. The data used relative search volume monthly from ten years (2013-2022). The data was then divided by the regional and before-after implementation the regulation of stunting reduction acceleration. Data were analyzed using ANOVA and t-student analysis. The findings showed that the relative search volume increased from the initial year before going down in 2018 and rose again during the pandemic. The region showed different RSV with p-value 0.001<0.05, and there was an effect of regulation implementation on RSV of child development. Google Trend is a management tool that can be used as a market analysis to assess the public interest in child de-velopment in healthcare services.